2011
DOI: 10.1016/j.ajog.2010.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin levels and risk of endometrial cancer: the prospective Nurses' Health Study

Abstract: Objective-Adiponectin, a protein secreted by adipose cells, is inversely associated with endometrial cancer (EC). Our objective was to assess pre-diagnostic adiponectin levels in relation to risk of EC.Study Design-Prospective nested case-control study within the Nurses' Health Study; cases 146, controls 377. Adiponectin was measured using enzyme-linked immunoabsorbant assay. Logistic regression analyses were performed adjusting for known EC risk factors.Results-Mean age at diagnosis was 64.6 years. Mean inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 20 publications
3
54
1
2
Order By: Relevance
“…Previous studies evaluating adiponectin and leptin levels and endometrial cancer risk have had various inclusion criteria regarding menopausal status and MHT use; one study included only postmenopausal women (13), whereas the others stratified by menopausal status (12,14) and women were either matched on MHT use (14) or current users were excluded (12)(13). Overall, these studies suggest an inverse association of adiponectin levels with endometrial cancer risk, which is consistent with the results from the current study, although some differences are noted.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies evaluating adiponectin and leptin levels and endometrial cancer risk have had various inclusion criteria regarding menopausal status and MHT use; one study included only postmenopausal women (13), whereas the others stratified by menopausal status (12,14) and women were either matched on MHT use (14) or current users were excluded (12)(13). Overall, these studies suggest an inverse association of adiponectin levels with endometrial cancer risk, which is consistent with the results from the current study, although some differences are noted.…”
Section: Discussionsupporting
confidence: 88%
“…Case-control studies have reported an inverse association; however, these studies used post-diagnostic serum and thus could not address temporality (8)(9)(10)(11). To date, only three prospective studies have been conducted; one study reported an inverse association with pre-diagnostic serum levels (12), whereas the other two reported no association (13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In a nested case-control study of male smokers an inverse association betweeen pre-diagnostic adiponectin and risk of renal cell carcinoma was observed, which accounted for a large proportion in the positive association between BMI and renal cell carcinoma [61]. On the other hand, no association between circulating adiponectin and risk of endometrial cancer, the cancer type that shows that strongest association with obesity, was observed in the Nurses Health Study, but the number of included cases was limited [62]. Interestingly, adiponectin, in particular HMW-adiponectin, has been associated with higher risk of hepatocellular carcinoma in two nested case-control studies of prospective cohorts including EPIC [63,64], but not in another nested case-control study [65].…”
Section: Adiponectinmentioning
confidence: 98%
“…Insulina bezpośrednio pobudza wzrost komórek zrębu endometrium na zasadzie ligand -receptor, niemiej jednak niewielka wiedza na temat dokładnego mechanizmu oddziaływania między adiponektyną, insuliną, leptyną i elementami układu IGF skłania do formułowania ostrożnych wniosków. Mimo jednoznacznych wyników badań, w których określano stężenia adiponektyny u chorujących na raka endometrium, nie udało się jednak wykazać przydatności prediagnostycznej określania stężenia tego białka w surowicy w definiowaniu ryzyka zachorowania [36]. Wydaje się zatem, że przypisywanie adiponektynie klu-czowej roli w patogenezie raka endometrium jest nieco przesadzone.…”
Section: Adiponektynaunclassified